A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Chou, Wen-Chen; Fan, Lan-Feng; Yang, Chang-Chang; Chen, Ying-Hsuan; Hung, Chin-Chang; Huang, Wei-Jen; Shih, Yung-Yen; Soong, Keryea; Tseng, Hsiao-Chun; Gong, Gwo-Ching; Chen, Hung-Yu; Su, Cheng-Kuan (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO2 (pCO2) during the daytime and lower pH but higher pCO2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low pCO2 across a diel cycle. We suggest that this distinct diel pattern in pH and pCO2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO2, in particular in a semienclosed setting.